2004
DOI: 10.1097/01.ccm.0000098029.65347.f9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality and quality of life after prolonged mechanical ventilation*

Abstract: Mortality rate after prolonged mechanical ventilation is high. Long-term mortality rate is associated with older age and poor prehospitalization functional status. Many survivors needed assistance after discharge from the hospital, and more than half still required caregiver assistance at 1 yr. Interventions providing support for caregivers and patients may improve the functional status and quality of life of both groups and thus need to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
193
2
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(224 citation statements)
references
References 45 publications
14
193
2
12
Order By: Relevance
“…Over 27% of blacks believed that 50% or more of persons receiving this life-sustaining treatment were returned to their normal activities, compared to 17% of non-Hispanic whites. In reality, 56% of patients who require mechanical ventilation for 48 h or more are dead at 1 year, and almost 60% of the survivors require caregiver assistance at 1 year 32 . This, of course, is in stark contrast to the popular representations of life-sustaining treatments 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Over 27% of blacks believed that 50% or more of persons receiving this life-sustaining treatment were returned to their normal activities, compared to 17% of non-Hispanic whites. In reality, 56% of patients who require mechanical ventilation for 48 h or more are dead at 1 year, and almost 60% of the survivors require caregiver assistance at 1 year 32 . This, of course, is in stark contrast to the popular representations of life-sustaining treatments 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The worse one-year mortality in the prolonged-weaning group is probably due to their higher hospital mortality. According to the literature, the oneyear mortality range in mechanically ventilated patients is 50 -70%, [26][27][28] and 63-78% in patients in weaning units. 29,30 These results confirm that mechanical ventilation weaning duration does not influence long-term outcome, as already suggested by Stauffer et al, 27 who found that long-term outcome was independent from overall ventilation duration.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilación mecánica prolongada En la bibliografía, existe variabilidad para definir ventilación mecánica prolongada (VMP): ≥ 48 horas, 19 ≥ 96 horas, 20 ≥ 7 días, 21,22 y ≥ 21 días. 23 En este estudio, consideramos VMP al período de ARM igual a 7 días o mayor.…”
Section: 18unclassified